1995
DOI: 10.1002/art.1780381008
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of chlamydia trachomatis biologic behavior in synovial membranes suppression of surface antigen production in reactive arthritis and reiter's syndrome

Abstract: Objective. To investigate the biologic state of Chlamydia and its surface antigen expression in the synovial membranes of patients with Chlamydia‐associated reactive arthritis/Reiter's syndrome (ReA/RS). Methods. Expression of chlamydial lipopoly‐saccharide (LPS), major outer membrane protein (MOMP), and elementary body (EB) antigens was studied by gold labeling immunoelectron microscopy on 6 synovial membrane and 2 synovial fluid (SF) pellet samples from 6 patients with Chlamydia‐associated arthritis. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 42 publications
3
65
0
3
Order By: Relevance
“…Besides the gene sequence for 16S rRNA, Bas et al (26) detected a major outer membrane protein (MOMP) gene sequence and 2 chlamydial plasmid sequences. Several investigators then reported obtaining positive PCR results for 16S rRNA (27,28). Gerard et al (29) took synovial specimens that tested positive for 16S rRNA by PCR and then further identified chlamydial gene products (glyQS, r-protein S5 and L5, and Hsp60) within a majority of these biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the gene sequence for 16S rRNA, Bas et al (26) detected a major outer membrane protein (MOMP) gene sequence and 2 chlamydial plasmid sequences. Several investigators then reported obtaining positive PCR results for 16S rRNA (27,28). Gerard et al (29) took synovial specimens that tested positive for 16S rRNA by PCR and then further identified chlamydial gene products (glyQS, r-protein S5 and L5, and Hsp60) within a majority of these biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of C. pneumoniae in persistent infection is characterized by an absence of culturability [7], in addition to altered bacterial RNA and protein levels [8][9][10][11], morphologically altered chlamydial bodies [8] and increased resistance to antimicrobials, such as azithromycin or clarithromycin, frequently used for the treatment of C. pneumoniae infection [12]. The mechanisms leading to persistent C. pneumoniae infection remain unclear; however, infection in reported cases occurred during an uncompleted developmental cycle with a lack of maturation of the EB, and an absence of bacterial metabolic activity caused a decrease in sensitivity to the antibiotics used.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydia, Yersinia, and Salmonella infect mainly epithelial cells and macrophages, and it is known that they can persist for a long time in macrophages. There is growing evidence that Chlamydia can be detected in synovial fluid and synovial membrane not only in acute, but also in chronic, forms of ReA (42). The detection of chlamydia1 DNA (43) and RNA (42,44) confirms that whole viable organisms are likely to be present.…”
Section: Bacterial Antigen Persisting In the Joint As The Cause Of Spmentioning
confidence: 94%
“…There is growing evidence that Chlamydia can be detected in synovial fluid and synovial membrane not only in acute, but also in chronic, forms of ReA (42). The detection of chlamydia1 DNA (43) and RNA (42,44) confirms that whole viable organisms are likely to be present. However, all attempts thus far to find Yersinia DNA in the joint have failed, in spite of the presence of Yersinia antigen detectable by immunologic techniques (45,46).…”
Section: Bacterial Antigen Persisting In the Joint As The Cause Of Spmentioning
confidence: 94%